2019
DOI: 10.1515/cti-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of 3D printing in chemistry education – analysis of earlier research and educational use through technological pedagogical content knowledge framework

Abstract: The focus of this systematic literature analysis is to provide a comprehensive review of earlier research on the utilisation of 3D printers in chemistry education. The objective is to offer research-based knowledge for developing chemistry education through following research questions: what kind of work has been done in the field of 3D printing in chemistry education; what kind of design strategies have been implemented; how 3D printing has been used in chemistry education research. The data consists of 47 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 52 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…Research on the use of 3D printing technologies in chemistry education has gained momentum especially after 2014. These studies generally focused on the importance of 3D printing technology in chemistry education, the design strategies applied in this field, and the way of application of this technology (Pernaa & Wiedmer, 2019). Regarding research environments, 3D printing has been limited to biomedical applications and engineering, but has enormous potential in chemical sciences as well (Gross et al, 2014).…”
Section: Findings 3d Printing Technology and Teaching Materials Samples In Chemistry Educationmentioning
confidence: 99%
“…Research on the use of 3D printing technologies in chemistry education has gained momentum especially after 2014. These studies generally focused on the importance of 3D printing technology in chemistry education, the design strategies applied in this field, and the way of application of this technology (Pernaa & Wiedmer, 2019). Regarding research environments, 3D printing has been limited to biomedical applications and engineering, but has enormous potential in chemical sciences as well (Gross et al, 2014).…”
Section: Findings 3d Printing Technology and Teaching Materials Samples In Chemistry Educationmentioning
confidence: 99%
“…Several discipline‐specific literature reviews on educational uses of 3DP have been published (e.g., chemistry education, Pernaa & Wiedmer, 2019; surgical education, Martelli et al, 2016). The discipline‐specific literature reviews identify important applications of 3DP to the discipline, focusing on the development and printing process of 3D printed tools and physical models that support working with discipline‐specific challenges.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies included in these reviews reported effects on learning. Many scholars have noted the need for ‘comprehensive student‐centred pedagogical models’ for using 3DP in education (Pernaa & Wiedmer, 2019, p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The use of additive manufacturing (3D printing) in educational contexts has grown exponentially in the past several years [1][2][3]. Within the educational community, 3D printing has two primary forms: usable laboratory equipment/experiments [4][5][6][7][8][9][10][11], and in-class demonstrations/models, including orbitals [12,13], surfaces [14,15], molecular models [16][17][18], biological molecules [19][20][21], and data visualization [22,23].…”
Section: Introductionmentioning
confidence: 99%